Social action to address the climate catastrophe of May 2024 in the Porto Alegre Metropolitan Region: developing a contingency plan to build socio-environmental resilience at the Filhos de Sepé settlement - Schreiner, Camila Traesel; Audibert, Alice; Telockenn, Elisangela; Carvalho, Jaime Roque Monteiro; Dalenogare, Isabel Cristina Monjelo Ribeiro; Engelmann, Janine de Almeida; Nunes, Letícia Rodrigues; Costa, Carolina Silveira; Coelho-de-Souza, Gabriela (Sustainability in Debate, 2025)
Extreme weather events are a consequence of climate change, whose effects have become more frequent and severe, as has been observed in the Porto Alegre Metropolitan Region (PAMR). In this socio-biodiverse area, communal areas, such as settlements resulting from agrarian reform, have been severely affected. Against this backdrop, the aim is to analyse the social action involved in creating a contingency plan for the Filhos de Sepé settlement, taking into account the associated impacts and strategies adopted. The methodology involved fieldwork and the systematic analysis of the participatory contingency planning stages. The settlement demonstrated responsiveness and solidarity with other settlements and territories by implementing strategies such as community kitchens, collective sewing, support brigades, animal rescue, and native seedling production. This historical social organisation, based on popular organisation, enabled the creation of a participatory contingency plan in response to organised civil society, thereby contributing to the socio-environmental resilience of PAMR territories.